2019
DOI: 10.1155/2019/6171532
|View full text |Cite
|
Sign up to set email alerts
|

Role of Customized Bus Services in the Transportation System: Insight from Actual Performance

Abstract: After attaining great prevalence from the end of 2013, customized bus (CB) transit services have experienced a huge decline in China. The feasibility of this new bus sharing system is thus being questioned. Therefore, it is imperative to investigate the actual role of CB services in the overall transportation system based on successful cases, as the role of the CB service determines its primary service object, system construction, marketing orientation, and even government function. To examine the role of CB s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Wang et al [2] found that CB is very attractive especially to commuters traveling in the peak hours because of its features in reducing travel time and coverage of spatiotemporal demand. It was also found that CB could serve as a supplement mode in the areas with low PT coverage.…”
Section: Customized Bus (Cb) Transitmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [2] found that CB is very attractive especially to commuters traveling in the peak hours because of its features in reducing travel time and coverage of spatiotemporal demand. It was also found that CB could serve as a supplement mode in the areas with low PT coverage.…”
Section: Customized Bus (Cb) Transitmentioning
confidence: 99%
“…Transit agencies thus promote demand responsive transit (DRT) as an alternative mode to elevate service quality by offering greater mobility and accessibility during the peak hours. With the rapid development of mobility as a service (MaaS) and personal mobile devices, an emerging DRT service, called customized bus (CB), has been initiated [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the literature focuses on two aspects of research on CB, namely, route planning ( Tong et al, 2017 ; Guo et al, 2019 ) and case (or factor) study ( Cao and Wang, 2016 ; Wang et al, 2019 ). There is little discussion of operational strategy or customer (or passenger) behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Xue [13] considered the uncertain factor of number of passengers at a bus stop in reality, introduced the uncertainty theory to construct an uncertain bi-level programming model of bus line allocation, and solved it using MATLAB. Other scholars [14][15][16][17][18] analyzed customized buses from the aspects of passenger flow prediction and influencing factors. However, in real life, the time for a vehicle to arrive at each stop is not fixed, and few studies regard it as an uncertain variable.…”
Section: Introductionmentioning
confidence: 99%